Pengaruh Tingkat Pengetahuan dan Sikap Terhadap Perilaku Ibu Tentang Pencegahan Stunting di Dolok Tomuan Wilayah Kerja Puskesmas Tiga Dolok - Silaen, Peterson Yosua; Sidabutar, Sondang; Pasaribu, Riada M; Simanjuntak, Tresia; Manalu, Putri Oktavia; Marpaung, Seri Anita; Barimbing, Diana (Jurkessutra : Jurnal Kesehatan Surya Nusantara, 2025)
ABSTRACT Stunting is one of the significant health issues in Indonesia, especially among toddlers. Stunting is a condition of impaired growth in children due to chronic malnutrition, leading to delayed physical growth and cognitive development. This study aims to analyze the influence of mothers' knowledge and attitudes on stunting prevention behaviors in the Dolok Tomuan area, Dolok Panribuan District, Simalungun Regency. This research employed a quantitative descriptive design with a cross-sectional approach. The study population comprised mothers with toddlers, with a sample size of 42 participants selected using simple random sampling. Data were collected through a questionnaire covering mothers' knowledge, attitudes, and behaviors related to stunting prevention.The results showed that the majority of mothers had good knowledge (85.7%) and positive attitudes toward stunting prevention (76.2%). Statistical tests using Chi-Square revealed a significant influence of mothers' knowledge and attitudes on their stunting prevention behaviors (p 0.01). This confirms that good knowledge and positive attitudes among mothers play a crucial role in improving stunting prevention behaviors in toddlers.This study recommends that health centers and the community should actively educate and raise mothers' awareness of the importance of child nutrition and health to prevent stunting. Further efforts in enhancing health education and facilities are essential to achieve better outcomes in stunting prevention in the future.Keywords: stunting, knowledge, attitude, behavior, prevention, toddlers